The hype about hydrogen : - Romm, Joseph J. (Island Press, 2005)
The Hype about Hydrogen offers a hype-free explanation of hydrogen and fuel cell technologies, takes a hard look at the practical difficulties of transitioning to a hydrogen economy, and reveals why, given increasingly strong evidence of the gravity of climate change, neither government policy nor business investment should be based on the belief that hydrogen cars will have meaningful commercial success in the near or medium term. Romm, who helped run the federal government's program on hydrogen and fuel cells during the Clinton administration, provides a provocative primer on the politics, business, and technology of hydrogen and climate protection.